Cardiac resynchronisation therapy is not associated with a reduction in mortality or heart failure hospitalisation in patients with non-left bundle branch block QRS morphology: meta-analysis of randomised controlled trials - Cunnington, Colin; Kwok, Chun Shing; Satchithananda, Duwarakan K; Patwala, Ashish; Khan, Muhammad A; Zaidi, Amir; Ahmed, Fozia Z; Mamas, Mamas A (Heart (British Cardiac Society), 2015)
ObjectivesRecently published clinical guidelines recommend cardiac resynchronisation therapy (CRT) for patients with heart failure (HF) with reduced LVEF and non-left bundle branch block (non-LBBB) QRS morphology. We sought to define the potential benefit of CRT in these patients through meta-analysis of randomised controlled trials (RCTs) that have reported outcomes in patients with non-LBBB QRS morphology.MethodsWe searched MEDLINE and EMBASE for RCTs of CRT that reported outcomes according to QRS morphology. We performed meta-analysis of these RCTs to assess the effect of CRT on the end points of death, HF hospitalisation, and the composite of death and HF hospitalisation.ResultsFive RCTs were analysed, including 6523 participants (1766 with non-LBBB QRS morphology). CRT was not associated with a reduction in death and/or HF hospitalisation in subjects with non-LBBB QRS morphology (HR 0.99 95% CI 0.82 to 1.20).ConclusionsCRT is not associated with a reduction in death or HF hospitalisation in patients with non-LBBB QRS morphology. Wide QRS with non-LBBB morphology remains an area of uncertainty for CRT, which is included in the recent European Society of Cardiology guidelines with a weaker strength of recommendation, but is not supported by a dedicated RCT.